2022
DOI: 10.1039/d1cp04443e
|View full text |Cite
|
Sign up to set email alerts
|

A chemical dynamics study of the reaction of the methylidyne radical (CH, X2Π) with dimethylacetylene (CH3CCCH3, X1A1g)

Abstract: The gas-phase reaction of the methylidyne (CH; X2Π) radical with dimethylacetylene (CH3CCCH3; X1A1g) was studied at a collision energy of 20.6 kJ mol-1 under single collision conditions with experimental results...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 108 publications
1
24
0
Order By: Relevance
“…Since the cost of different ab initio methods scales differently with the number ( N ) of basis functions (roughly N 4 for DFTs and N 5 for MP2) and the number of basis functions tested in this study spans a large range (between 26 for LANL2DZ and 155 for aug-cc-pVTZ), the cost of tested candidate methods varies dramatically. As previous AIMD studies have demonstrated, their results are extremely sensitive with respect to the method (e.g., MP2 vs DFT). Further, since the computationally efficient method is selected based on optimized structures, while AIMD simulations traverse through unoptimized structure, it is possible that the computationally efficient method with the smallest RMSD performs poorly in AIMD. ,, Behaviors such as convergence failures, total energy jumps, and/or unphysical charge distributions have been previously reported for AIMD with DFTs. , Therefore, one DFT functional, the rCAM-B3LYP functional, and one MP2 method, FC-MP2, are recommended. For the former, rCAM-B3LYP functional reports the overall smallest RMSD with pc-2 (5.3 kJ/mol, 105 basis functions), followed by cc-pVDZ (5.8 kJ/mol, 55 basis functions) and Sapporo-DZP-2012 (6.0 kJ/mol, 80 basis functions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the cost of different ab initio methods scales differently with the number ( N ) of basis functions (roughly N 4 for DFTs and N 5 for MP2) and the number of basis functions tested in this study spans a large range (between 26 for LANL2DZ and 155 for aug-cc-pVTZ), the cost of tested candidate methods varies dramatically. As previous AIMD studies have demonstrated, their results are extremely sensitive with respect to the method (e.g., MP2 vs DFT). Further, since the computationally efficient method is selected based on optimized structures, while AIMD simulations traverse through unoptimized structure, it is possible that the computationally efficient method with the smallest RMSD performs poorly in AIMD. ,, Behaviors such as convergence failures, total energy jumps, and/or unphysical charge distributions have been previously reported for AIMD with DFTs. , Therefore, one DFT functional, the rCAM-B3LYP functional, and one MP2 method, FC-MP2, are recommended. For the former, rCAM-B3LYP functional reports the overall smallest RMSD with pc-2 (5.3 kJ/mol, 105 basis functions), followed by cc-pVDZ (5.8 kJ/mol, 55 basis functions) and Sapporo-DZP-2012 (6.0 kJ/mol, 80 basis functions).…”
Section: Resultsmentioning
confidence: 99%
“…64−66 Further, since the computationally efficient method is selected based on optimized structures, while AIMD simulations traverse through unoptimized structure, it is possible that the computationally efficient method with the smallest RMSD performs poorly in AIMD. 15,67,68 Behaviors such as convergence failures, total energy jumps, and/or unphysical charge distributions have been previously reported for AIMD with DFTs. 15,67 Therefore, one DFT functional, the rCAM-B3LYP functional, and one MP2 method, FC-MP2, are recommended.…”
Section: Selecting a Computationally Efficientmentioning
confidence: 85%
“…Following the astrophysical detection of c-C 3 HC 2 H (Cernicharo et al 2021), a mechanistic study of its formation found that c-C 3 HC 2 H may form through a gas-phase reaction between c-C 3 H 2 and the ethynyl radical (Fortenberry 2021). These results open a veritable Pandora's box for further astrochemical analysis regarding the formation of c-C 3 H 2 and its family of derivatives (He et al 2022;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The chemical scheme of formation of these species is based on neutral-neutral reactions and is discussed in detail in Appendix D. Briefly, reactions of CCH and CN with c-C 5 H 6 and C 6 H 6 lead to the CCH/CN derivatives of each cycle (Balucani et al , 1999;Jones et al , 2010). The formation of the precursor hydrocarbon cycles c-C 5 H 6 and C 6 H 6 relies on reactions between small hydrocarbon radicals and butadiene (CH 2 CHCHCH 2 ), which acts as a key species that opens the chemistry to hydrocarbon cycles at 10 K (He et al , 2020a;Jones et al , 2011). Additional routes to the CCH/CN derivatives of c-C 5 H 6 involve reactions of C 3 H/C 2 N with butadiene.…”
Section: Chemistry Of Cycles In Tmc-1mentioning
confidence: 99%